Analisis Biaya Produksi dan Profitabilitas Pada Pabrik Gula Kebon Agung Malang - Anggraeni, Ayu Dewi; jadi, Moel (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Sugar is one of the strategic commodities in Indonesian economy. National sugar production comes mostly from sugar production in East Java. It is based on data from East Java Plantation Office (2007), which states that the rapid growth of the sugar industry in East Java province put Java as the largest contribution to the national sugar production reached 2.31 million tons (over 47 percent) in in 2006. This study aims to determine how the cost of production that occurred as a reference for determining the selling price and to find out how the profitability of the acquired PG Kebun Agung Malang 2010-2012. This research is descriptive research with quantitative approach. Object of this study is PG Kebun Agung Malang. Sources of data used in this study is a secondary data source, ie from production data, sales data, and the income statement. Data collection techniques used are documentation. Analytical approach to the calculation of cost of production using components of the cost of materials, direct labor costs, and factory overhead costs. Financial performance analysis in this study using the approach break event analysis (Break Event Point). The results showed that the cost of production that occurred as a reference for determining the selling price in the period 2010-2012 PG Kebon Agung Malang has increased, it indicates that the company can set prices according to production costs incurred. The profitability derived from PG Kebon Agung Malang in 2010-2012 has decreased, this is due to both fixed costs and operational costs have increased and this will affect the revenue received has decreased. Keyword :Production Cost and Profitability.